Multicultural Values: An Analysis of the Indonesian Literacy Disregard - Slamet - Slamet (Universitas of Muhammadiyah Makassar, 2020)
The background of this study is a pluralistic and multicultural Indonesian nation-state from culture, religion, ethnicity, ethnicity, social, and territorial heritage as a prehistoric / pre-literacy era that often arises due to conflict due to friction from a variety of diversity, so there needs to be a solution as a solution to the application of multicultural values to an educational institution. The purpose of this study is to describe: 1) the social system; 2) belief system; 3) science and technology; 4) artistry; 5) agriculture; and 6) shipping. This type of research is designed using a descriptive approach, while the form of research uses a content analysis model, then in practice, it refers to the content analysis procedure. The results of the study concluded that one of the major problems of this nation is the awareness of the identity of a nation-state. This is due to 2 (two) waves of social change, namely globalization and democracy. At the global level, in addition to the existence of world powers such as in politics and trade, there is also a power that wants people to have an awareness of their identities, so we need a unity of the nation that is awareness in the container and frame of the Unitary State of the Republic of Indonesia.Keywords: Multicultural Values;prehistoric Latar belakang kajian ini adalah negara-bangsa Indonesia yang plural dan multikultur dari budaya, agama, etnis, suku, sosial, dan kewilayahan sebagai warisan jaman prasejarah/praaksara yang sering muncul adanya konflik disebabkan oleh adanya gesekan dari berbagai keragaman, sehingga perlu adanya solusi sebagai jalan pemecahan dengan penerapan nilai-nilai multikultur pada sebuah institusi pendidikan. Tujuan kajian ini adalah mendeskripsikan: 1) sistem sosial kemasyarakatan; 2) sistem kepercayaan; 3) ilmu pengetahuan dan teknologi; 4) kesenian; 5) pertanian; dan 6) pelayaran. Jenis penelitian didesain dengan menggunakan pendekatan deskriptif, sedangkan bentuk penelitian digunakan model analisis isi (content analysis), maka dalam pelaksanaannya mengacu pada prosedur analisis isi. Hasil penelitian diperoleh simpulan bahwa salah satu masalah besar bangsa ini adalah kesadaran identitas suatu negara-bangsa. Hal ini disebabkan adanya 2 (dua) gelombang perubahan sosial, yaitu globalisasi dan demokrasi. Pada tingkat global selain adanya kekuatan-kekuatan dunia seperti dalam bidang politik dan perdagangan, muncul pula kekuatan yang menginginkan orang memiliki kesadaran akan identitasnya, maka diperlukan sebuah persatuan bangsa yaitu kesadaran dalam wadah dan bingkai NKRI.Kata kunci: Nilai-Nilai Multikulrutal; Prasejarah